The Political Economy of Benefits and Costs: A Neoclassical Approach to Distributive Politics - Weingast, Barry R.; Shepsle, Kenneth A.; Johnsen, Christopher (Journal of Political Economy, 1981)
This essay offers a rational political explanation for the notorious inefficiency of pork barrel projects with an optimization model of legislative behavior and legislative institutions. The model emphasizes the (economically arbitrary, from a welfare point of view) importance of the geographic incidence of benefits and costs owing to the geographic basis for political representation. We explore the implications of a legislator's objective function and derive conditions under which a representative legislature will select an omnibus of projects each of which exceeds the efficient scale.